Identification and quantification of microplastic particles in drinking water treatment sludge as an integrative approach to determine microplastic abundance in a freshwater river. (1st October 2021) - Siegel, Henrik; Fischer, Franziska; Lenz, Robin; Fischer, Dieter; Jekel, Martin; Labrenz, Matthias
Abstract: Microplastic (MP) has been detected ubiquitously in freshwater systems. Until now MP sampling, however, is predominantly based on short-term net or pumping and filtration systems which can only provide snapshots of MP abundance; especially in flowing water bodies. To improve representativeness in the determination of MP occurrences in these aquatic compartments, an integrative approach that covers larger water volumes for a longer period of time is required. In this regard, surface water supplied drinking water treatment plants (DWTPs) represent an opportunity. In DWTPs, suspended solids from thousands of cubic metres of raw water are continuously removed over several hours and enriched in coagulation/flocculation and filtration processes. Our hypothesis was that MP is also removed to a full extent, like suspended solids, and that an integrative approach for identification and quantification in raw water can be derived from the analysis of MP in the treatment sludge. To prove this hypothesis, treatment sludge from a riverside DWTP (Warnow river, North-Eastern Germany) was analysed for MP > 50 μm. A sample purification protocol overcoming potential matrix effects caused by coagulants and flocculants was developed and validated. MP was analysed using micro-Raman spectroscopy. MP occurrence determined for the Warnow river was compared with in situ reference sampling using an established pumping and filtration system at relatively stable flow conditions. As result, the number of MP particles derived from treatment sludge was extrapolated to 196 ± 42 m −3 for the Warnow river and is statistically insignificantly different from 233 ± 36 m −3 identified by conventional water sampling. In addition, the polymer distribution and particles shape indicated the validity of the integrative concept. Consequently, the determination of MP abundance for freshwater systems based on DWTP treatment sludge represents an adequate method to estimate MP concentrations in flowing waters in an integrative way. Graphical abstract: Image 1 Highlights: Riverside MP abundance was integratively determined by DWTP sludge analysis. A purification protocol was developed and validated for spectroscopic MP detection. Results reflect MP concentration and composition derived from reference samplings. Integrative approach useful for long term monitoring of MP loads in rivers. Abstract : MP abundance for freshwater systems based on DWTP treatment sludge represents an adequate method to estimate MP concentrations in flowing waters in an integrative way.